Knightjonesia, a new genus (Polychaeta: Spirorbidae) with a winged opercular peduncle, and its taxonomy - Pillai, T. Gottfried (Zootaxa, 2009)
It had hitherto been assumed in publications on serpulimorph systematics that spirorbids are characterized by an operculum borne on a wingless peduncle. However, while examining various spirorbid collections in the Natural History Museum, London, it was found that the type specimens of Helicosiphon platyspira Knight-Jones, 1978 possess a winged opercular peduncle, a character that had hitherto been used to distinguish between other serpulimorph genera. Accordingly, Helicosiphon platyspira is transferred to a new genus, Knightjonesia, in which the opercular peduncle is winged, in contrast with Helicosiphon in which it is wingless.